Analisis Efektifitas Dan Efisiensi Penggunaan Anggaran Pada Paroki Roh Kudus Nelle Keuskupan Maumere - Maria Viviana Nurak Lewar; Tobias Joni Temu; Elisabet Luju; Yohanes Chrisantus Servrianus Moan Jawa (Jurnal Projemen UNIPA, 2025)
The research titled "Analysis of the Effectiveness and Efficiency of the Use of the Parish Budget of the Holy Spirit Nelle" aims to analyze the level of effectiveness and efficiency in the use of the budget at the Holy Spirit Nelle Parish during a specific reporting period. The analysis is conducted by comparing the activity targets and budget with the actual realization. The results show that the average effectiveness of activities is only 45.95%, indicating that most activities have not been optimally achieved. Meanwhile, the efficiency of budget utilization is recorded at 29.48%, which shows a low level of spending compared to the allocated funds. These findings indicate a gap between the planning and implementation of parish programs. Some programs have not been realized at all despite having a budget allocated. Therefore, improvements are needed in program planning, adjustments in budget allocations according to implementation capacity, as well as strengthening the monitoring and evaluation system to enhance accountability and financial performance of the parish moving forward.